2019
DOI: 10.2147/ott.s196865
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA <em>DLX6-AS1</em> promotes the proliferation, invasion, and migration of non-small cell lung cancer cells by targeting the <em>miR-27b-3p/GSPT1</em> axis</p>

Abstract: Background: Non-small cell lung cancer (NSCLC) has a significant impact on human health. The aim of this study was to explore the role of long non-coding RNA DLX6-AS1 in the proliferation, migration, and invasion of NSCLC cells. Methods: The expression of DLX6-AS1 in NSCLC tumor tissues and cell lines was examined by qRT-PCR. The effects of DLX6-AS1 knockdown on cell proliferation, migration, and invasion we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
(26 reference statements)
1
32
1
Order By: Relevance
“…Therefore, based on the ceRNA hypothesis, we further searched for the co-expressed mRNAs and miRNAs associated with lncRNA RP11-421L21.3 and finally discovered several miRNAs (miR-1, miR-128-3p, miR-150-5p, miR-27b-3p, and miR-613), which were correlated with the oncogenesis of NSCLC. Accumulating studies have demonstrated that these miRNAs were down-regulated in NSCLC tissues and could be participated in regulating the proliferation, invasion and metastasis of NSCLC cells through various pathways (Li J. et al, 2016;Chiu et al, 2017;Zheng et al, 2017;Jiang et al, 2018;Pan et al, 2018;Dai et al, 2019;Sun et al, 2019). However, there were no differences in expression levels of lncRNA RP11-390P2.4 and lncRNA RP11-421L21.3 between NSCLC tissues and adjacent non-cancerous tissues in our study.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Therefore, based on the ceRNA hypothesis, we further searched for the co-expressed mRNAs and miRNAs associated with lncRNA RP11-421L21.3 and finally discovered several miRNAs (miR-1, miR-128-3p, miR-150-5p, miR-27b-3p, and miR-613), which were correlated with the oncogenesis of NSCLC. Accumulating studies have demonstrated that these miRNAs were down-regulated in NSCLC tissues and could be participated in regulating the proliferation, invasion and metastasis of NSCLC cells through various pathways (Li J. et al, 2016;Chiu et al, 2017;Zheng et al, 2017;Jiang et al, 2018;Pan et al, 2018;Dai et al, 2019;Sun et al, 2019). However, there were no differences in expression levels of lncRNA RP11-390P2.4 and lncRNA RP11-421L21.3 between NSCLC tissues and adjacent non-cancerous tissues in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…According to the pathological classification, lung cancer can be classified into small cell lung cancer (SCLC) and non-small cell lung cancer (NSCLC) and approximately 80% of lung cancer cases are non-small cell lung cancer (NSCLC) (Siegel et al, 2019). Despite many improvements developed in diagnostic techniques and treatment strategies, the prognosis of NSCLC is still poor with a 5-year overall survival rate less than 20% (Ramalingam et al, 2011;Sun et al, 2019). As a majority of NSCLC patients are diagnosed at an advanced stage in a majority of patients, it may be the primary reason behind responding to the high mortality rate associated with this disease (Siegel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Luciferase reporters were designed and reporter assay was performed as previously described. 20 The association between LINC00665 and miR-1224-5p or between miR-1224-5p and SND1 was tested by using the Dual-Luciferase Reporter Assay System (Promega, Madison, WI). In brief, 5000 DU-145 cells per well were seeded into 24-well plates and transfected with pmirGLO reporter (Promega) containing wild-type (wt) or mutant (mut) LINC00665 or SND1-3Ęš-UTR region and miR-1224-5p mimics using Lipofectamine 3000 reagent (Invitrogen).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…On the other hand, the predicted Lnc DLX6-AS1 mutation mapped within the intron 1 sequence and might affect the acceptor splicing site ctgcgagtgcgg (according to SplicePort: An Interactive Splice Site Analysis Tool, http://spliceport.cbcb.umd.edu/; Cutoff=0.643; Score=0.888). As recently documented, the expression of lnc DLX6-AS1 was related to important tumor features (26). Remarkably, DLX6-AS1 mRNA expression was detected within exosome vesicles, according to the repository exoRBase database (exorbase.org) of circular RNA (circRNA), long non-coding RNA (lncRNA) and messenger RNA (mRNA) derived from RNA-seq data analyses of human liquid biopsies derived exosomes.…”
Section: Resultsmentioning
confidence: 87%
“…The Proline insertion was localized in a Proline-rich region composed in humans by 9 residues, at N-terminus of the mature protein, not affecting Hox and Abdominal A superfamily functional domains. While DLX6 (Distal-Less Homeobox 6) gene was not involved in cancer, differently, lnc DLX6-AS1 was very recently deeply investigated, promoting tumorigenesis in pancreatic (35), colorectal (36), ovarian (37), lung (38), gastric (39) and liver (40) cancers. These contributions pointed for a role of this lncRNA in proliferation and metastasis induction and also suggested DLX6-AS1 as a potential therapeutic target (41).…”
Section: Discussionmentioning
confidence: 99%